Developing self-perpetuating social learning: moving from constructive intervention to more autonomous group learning for drip irrigation in Morocco - Harvey, Blane; Ensor, Jonathan; Garside, Ben; Woodend, John; Naess, Lars Otto; Carlile, Liz (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
Moroccan farmers are becoming more involved in managing supply chains, notably through local and regional cooperatives, particularly for milk. However, despite the state’s attempts to transfer responsibilities to associations of water users, it retains control of large-scale irrigation schemes. In addition, a decline in surface water available for such schemes has prompted farmers to use groundwater from individual tube wells. Meanwhile, government programmes to relieve water scarcity with drip irrigation technology have not had good uptake from farming communities. The Moroccan branch of the agricultural research centre for development, CIRAD, wanted to help small-scale farmers to better understand drip-irrigation and plan their own group projects. The aim was to use land in ways that better suited the farmers and to encourage farmers to take more ownership of the process.